PENGARUH PENGGUNAAN POWERT POINT PADA PELAJARAN BIOLOGI TENTANG KEANEKARAGAMAN HAYATI TERHADAP PENINGKATAN HASIL BELAJAR DAN AKTIFITAS SISWA DI KELAS X-MIA-1 MADRASAH ALIYAH NEGERI BINJAI SEMESTER GANJIL TAHUN PELAJARAN 2021/2022 - Fauziah Fauziah (JGK (Jurnal Guru Kita), 2023)
The Effect of Using Power Point in Biology Lessons About Biodiversity on Increasing Learning Outcomes and Student Activities in Class X-Mia-1 Madrasah Aliyah Negeri Binjai Odd Semester 2021/2022 Academic Year. This research is using a type of quantitative research with 36 respondents. Management of hypothesis testing data using product moment analysis and t test. The results showed that the Effect of Using Power Point in Biology Lessons About Biodiversity on Increasing Student Learning Outcomes in Class X-MIA-1 Madrasah Aliyah Negeri Binjai Odd Semester 2021/2022 Academic Year, this can be seen from the results of the calculation in the first cycle between the scores pre test with MID test scores obtained Produc Moment Correlation of 0.720 and t test of 6.396, in the second cycle between Block I test scores and Odd Semester test scores obtained Produc Moment Correlation of 0.856 while r table is 0.478, and t test is 10.204 greater from t table of 2.725. The Effect of Using Power Point in Biology Lessons About Biodiversity on Increasing Student Activity in Class X-MIA-1 Madrasah Aliyah Negeri Binjai Odd Semester 2021/2022 Academic Year, this can be seen from the results calculated in the first cycle between the pre-test questionnaire scores and the scores the MID test obtained a Produc Moment Correlation of 0.665, and the t test of 5.492 and between the post test questionnaire scores and the Odd Semester test scores obtained a Produc Moment Correlation of 0.857 while the r table was 0.478, and the t test was 10.278 which was greater than the t table of 2.725.